Combining natural gas recovery and CO2-based geothermal energy extraction for electric power generation. (1st July 2020) - Ezekiel, Justin; Ebigbo, Anozie; Adams, Benjamin M.; Saar, Martin O.
Highlights: Dual-purpose utilization of CO2 : 1) extracting natural gas and 2) geothermal energy, while storing all CO2 (CCUUS). Partially depleted natural gas reservoirs are typically suitable for CO2 -based geothermal energy extraction. A CO2 flowrate of 110 kg/s results in a net power of 2 MWe for the highly scalable small system considered. The technology can extend the useful lifetime of a (previous) natural gas field. Abstract: We investigate the potential for extracting heat from produced natural gas and utilizing supercritical carbon dioxide (CO2 ) as a working fluid for the dual purpose of enhancing gas recovery (EGR) and extracting geothermal energy (CO2 -Plume Geothermal – CPG) from deep natural gas reservoirs for electric power generation, while ultimately storing all of the subsurface-injected CO2 . Thus, the approach constitutes a CO2 capture double-utilization and storage (CCUUS) system. The synergies achieved by the above combinations include shared infrastructure and subsurface working fluid. We integrate the reservoir processes with the wellbore and surface power-generation systems such that the combined system's power output can be optimized. Using the subsurface fluid flow and heat transport simulation code TOUGH2, coupled to a wellbore heat-transfer model, we set up an anticlinal natural gas reservoir model and assess the technical feasibility of the proposed system. The simulations show that the injection of CO2 for natural gas recovery and for the establishment of a CO2 plume (necessary for CPG) can be conveniently combined. During the CPG stage, following EGR, a CO2 -circulation mass flowrate of 110 kg/s results in a maximum net power output of 2 MWe for this initial, conceptual, small system, which is scalable. After a decade, the net power decreases when thermal breakthrough occurs at the production wells. The results confirm that the combined system can improve the gas field's overall energy production, enable CO2 sequestration, and extend the useful lifetime of the gas field. Hence, deep (partially depleted) natural gas reservoirs appear to constitute ideal sites for the deployment of not only geologic CO2 storage but also CPG.